An abstraction layer enabling pervasive hardware-reconfigurable systems. (2018) - Cilardo, Alessandro; Mazzocca, Nicola; Prinetto, Paolo
Field-programmable gate array technologies are creating a new range of challenges for pervasive and ubiquitous systems. Revisiting and extending approaches borrowed from the purely software domain is a fundamental opportunity in this scenario. In particular, this paper addresses code mobility, a well-established approach used to dynamically adapt a distributed system based on the actual application needs, and extends it to a deep code mobility concept, allowing 'logical' hardware components to be migrated across a pervasive infrastructure. The work presents the architecture and the prototype implementation of a reconfigurable computing framework providing full support to deep code mobility through an abstraction layer which exposes a portable view of the underlying reconfigurable hardware. The paper then thoroughly discusses two application scenarios, hardware-accelerated distributed data mining and autonomous online testing, confirming the impact of deep code mobility in real-world pervasive computing contexts.